Assessing the Asymmetric Impact of Oil Price on Islamic Stocks in Malaysia: New Evidence from Non-Linear Ardl - Abubakr Badeeb, R.; Lean, H. H. (Universiti Sains Islam Malaysia, 2024)
This paper examines the asymmetric impact of oil price on Malaysia Islamic stocks. Using non-linear ADRL cointegration methodology, the paper finds evidence suggesting that ignoring the intrinsic nonlinearities may lead to misleading inference. In particular, the results reveal significant differences in the responses of Islamic stocks positive or negative changes of the oil price in both the long and short- run time horizons. Therefore, the use of the asymmetric ADRL model contributes to the understanding of non-linear dynamics between oil price and Islamic stocks. This result leads to more efficient investment decision for investors and other market participants, by managing their investments and minimize their portfolio risks. Investors should respond asymmetrically to the increase and decrease of oil price when investing Islamic stocks in Malaysia.